Stability Analysis of l-Power Reciprocal Functional Equation in Intuitionistic Fuzzy Banach Spaces - Sadani, Idir (Universitas Brawijaya, 2024)
In this study, we explore the generalized Hyers-Ulam-Rassias stability of a l-power reciprocal functional equation in Intuitionistic Fuzzy Banach Spaces.